Utilization of Indigofera tinctoria L. Waste for the Production of Environmentally Friendly Biobriquettes - Joko Waluyo; Fachri Candra Abimanyu; Anindhea Sitta Kusuma Wardhani; Dhiah Cendikia Pradani; Fahri Chandra Prasetyo; Frizas Yardena Widharmo; Helvita Fajar Utami; Septian Warsito Utomo (Program studi Teknik Kimia UNS, 2026)
Indigofera tinctoria L. is a natural source of blue dye widely used in various industries, particularly in the textile sector. One of the industries utilizing Indigofera tinctoria L. as a natural dye is CV Indigo Biru Baru, based in Puron Village, Bulu District, Sukoharjo. This company specializes in the production of batik fashion. The waste generated from processing Indigofera tinctoria L. produces significant volumes of organic material, which often goes underutilized and poses a potential environmental pollution risk. This study aims to optimize this waste by converting it into biobriquettes as an alternative fuel source. The production process involves pyrolyzing the waste at temperatures of 300–350℃ for 2 hours, followed by binding with tapioca starch paste at a 10:1 ratio, molding, and quality testing based on SNI (Indonesian National Standard). The biobriquette characterization includes proximate analysis, calorific value measurement, drop test, and yield evaluation. The results showed a moisture content of 6.9665%, ash content of 7.2025%, volatile matter content of 33.522%, fixed carbon content of 52.309%, and a calorific value of 5438.902 cal/g. Meanwhile, the hardness test indicated that only 0.042% of the mass was lost during the drop test, demonstrating excellent physical durability. With its high calorific value and superior physical characteristics, this biobriquette exhibits great potential as a renewable fuel to support sustainable energy transition in Indonesia.